Milk productivity and reproductive abilities of black-and-white cows of different lines - S. V. Titova; V. A. Zabiyakin (Аграрная наука Евро-Северо-Востока, 2020)
The article presents the results of the research on the comparative study of the main economically valuable traits of dairy cattle of various origin. The population of Holstein cows of black-and-white breed was taken as the object of the study. Source material for the research was provided by data of breeding records (n = 4848) of cows from breeding plant "Semyonovsky", Medvedevsky district, Mari El Republic. The breeding stock of the herd was presented by four lines: Vis Bek Idial 1013415 – 55.6 %, Reflection Sovering 198998 – 36.9 %, Montvik Chieftain 95679 – 6.7 % and Siling Trijun Rokit 252803 – 0.3 %. Animals of V. B. Idial line were most productive. They were superior to the representatives of other lines: in milk yield by 448-891 kg of milk (7.1-15.2 %) (p>0.99), in milk fat yield – by 17.5-35.0 kg (7.3-15.7 %) (p>0.99), in milk protein – by 4.7-28.6 kg (7.4-15.5 %) (p>0.99) and they had a high coefficient of milking capacity of 1323 kg. Animals of all lines except S. T Rokit line were characterized by a uniform (stable) lactation curve, the coefficient of lactation stability was 93 %. The lowest age of the first calving was observed in animals of the R. Sovering line (26.5 months), the highest – in the S. T. Rokit line (30.7 months). The duration of the service period in the V.B. Idial line was 129.4 days, that was higher than this indicator for other lines by 8.3-11 days (6.8-9.3 %) (p>0.95-0.99). The duration of the calving interval in all studied lines exceeded the optimal one (365 days) and changed in accordance with the change of the service period. A high index of fecundity was in cows of V. B. Ideal line (45.3), a low index - in S. T. Rokit line (37.2). In the studied lines, the coefficient of reproductive ability that characterizes the fertility of cows was 0.90-0.92, in S. T. Rokit line – 0.84.